Pendampingan Pembukaan Pariwisata Baru Pada Bumdes Mekar Sejahtera Desa Cibitung Menggunakan Metode Participatory Action Research - Moh. Asep Suharna; Amar Hamzah (Jurnal TUNAS, 2022)
The development of the tourism sector is one of the components of national development that aims to develop an area. Village-Owned Enterprises (BUMDes Mekar Sejahtera) located in Cibitung village have a business focus on the tourism sector. One of the tourism potentials in Cibitung Village is the Batu Lawang Pine Forest Camp Tour which is planned to be opened, located in Sukanagara Hamlet. In this period of service, the author seeks to accompany the role of BUMDes to open tourism. Mentoring is a way to invite the community. The technique in Mentoring carried out by the author is Participatory Action Research. With this service activity, the opening of the Batu Lawang Pine Forest camp tour was welcomed by the community. However, there is still no access to the location that still needs to be addressed. In the future, the Mekar Sejahtera BUMDES must provide road access and water and toilet facilities so that the opening of Batu Lawang Pine Forest Camping Tour will attract more visitors., while the results and conclusions in the form of simple present tense.